Super-hydrophobic flame-retardant fiber and preparation method thereof
Super-salicone prepared by reacting pretreated polyacrylonitrile with diallyl chlorophosphite and 5-mercaptosalicylic acid and blending with modified silica, and finishing with acrylamide and perfluorooctyl ethylene. Hydrophobic flame retardant fiber solves the problem of single function of fibers in outdoor activities, and achieves the improvement of flame retardant, hydrophobic, antibacterial and anti-ultraviolet properties.
Patent Information
- Application Number
- CN202411621591.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-11-14
AI Technical Summary
Existing fibers lack the versatility of flame retardant, hydrophobic and antibacterial activities in outdoor activities, making it difficult to meet the safety and practical needs of outdoor products.
Modified polyacrylonitrile grafted melamine with diallyl chlorophosphite and react with 5-mercaptosalicylic acid to produce modified polyacrylonitrile, combined with modified silica, using acrylamide and Perfluorooctyl ethylene finishes to produce superhydrophobic flame retardant fibers, achieving the flame retardant, hydrophobic, antibacterial and ultraviolet resistance of the fibers.
It has achieved good flame retardant, hydrophobic, antibacterial and ultraviolet resistance of fibers, and broadened the application prospects of fibers in the field of high-performance textiles.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of fibers, in particular to a super hydrophobic flame retardant fiber and a preparation method thereof. Background Art
[0002] In the development of textile material technology, the pursuit of multifunctionality has become an important research direction. Although traditional fibers can meet daily needs to a certain extent, they often lack special functions, which limits their applicability in different environments.
[0003] With the popularity of outdoor activities, people's demand for outdoor products is gradually increasing. The safety and practicality of outdoor products such as tents and outdoor clothing have become one of people's concerns. In outdoor activities, flame-retardant fiber products can effectively avoid the safety hazards caused by activities such as picnics and bonfire parties; super-hydrophobic fiber products can help people cope with severe outdoor weather such as rain and snow at any time. Therefore, a fiber with both hydrophobic and flame-retardant properties is needed. Similarly, in order to further broaden the application field of the fiber, other properties can also be given to the fiber, such as antibacterial and UV resistance. The present invention prepares a super-hydrophobic flame-retardant fiber, which not only has excellent flame retardancy and hydrophobicity, but also has lasting antibacterial and UV resistance properties, overcoming the problem of single function in the prior art, and thus has important application prospects in the field of high-performance textiles. Summary of the invention
[0004] The object of the present invention is to provide a super hydrophobic flame retardant fiber and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A super hydrophobic flame retardant fiber is prepared by grafting melamine onto pretreated polyacrylonitrile, reacting with diallyl chlorophosphite, and then reacting with 5-mercaptosalicylic acid to obtain modified polyacrylonitrile; reacting silica with tetramethylguanidinopropyltrimethoxysilane to obtain modified silica; blending the modified polyacrylonitrile and the modified silica for spinning, and finally finishing with acrylamide and perfluorooctylethylene to obtain the super hydrophobic flame retardant fiber.
[0006] A method for preparing a super hydrophobic flame retardant fiber comprises the following preparation steps: (1) Pretreated polyacrylonitrile, melamine, N,N-dicyclohexylcarbodiimide, N,N-dimethylformamide, and boric acid were mixed uniformly in a mass ratio of 1:1-2:0.5-0.8:100-120:0.1-0.2, reacted at 60°C for 4 hours, cooled to room temperature, added with dichloromethane 100-120 times the mass of pretreated polyacrylonitrile, filtered and washed with pure water for 3-4 times, and dried at 60°C for 12-14 hours to obtain melamine-modified polyacrylonitrile; (2) Mix melamine-modified polyacrylonitrile, acetonitrile and triethylamine in a mass ratio of 1:20-30:0.1-0.3 to obtain solution A; prepare diallyl chlorophosphite with acetonitrile to prepare solution B with a concentration of 2-3 g / mL; add solution B (0.02-0.04 times the volume of solution A) dropwise to solution A at 80°C at a rate of 0.25 mL / min. After the addition is completed, continue the reaction for 6-8 hours, add dichloromethane (40-50 times the mass of the melamine-modified polyacrylonitrile), filter and wash with pure water for 3-4 times, and dry at 60°C for 12-14 hours to obtain a modified polyacrylonitrile precursor; (3) The modified polyacrylonitrile precursor, 5-mercaptosalicylic acid, and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:2-3:20-30, 0.1-0.3 times the mass of the modified polyacrylonitrile precursor of 2,2-dimethoxy-2-phenylacetophenone is added, ultrasonication is performed at 20-40kHz for 20-30 minutes, ultraviolet light is irradiated at room temperature for 30 minutes, and the ultraviolet light power is 500w. Then, 40-50 times the mass of the modified polyacrylonitrile precursor of dichloromethane is added, the mixture is filtered and washed with pure water for 3-4 times, and dried at 60°C for 12-14h to obtain modified polyacrylonitrile; (4) Mix silica and anhydrous ethanol in a mass ratio of 1:20-30, disperse them ultrasonically at 20-40kHz for 20-30min, add a mixed solution of tetramethylguanidinopropyltrimethoxysilane in an equal volume to anhydrous ethanol, stir at 60-80°C for 4h at a stirring speed of 400-500r / min, filter after stirring, wash with pure water for 5-7 times, and dry at 60°C for 6-8h to obtain modified silica; (5) Mixing modified silica and N,N-dimethylformamide in a mass-to-volume ratio of 1-5:100, ultrasonically treating at 20-40 kHz for 30-40 min, adding modified polyacrylonitrile in an amount 10-20 times the mass of the modified silica, stirring at 5-10° C. for 2-3 h at a stirring speed of 400-600 r / min, and ultrasonically defoaming at 20-40 kHz for 30-40 min to obtain a spinning solution; (6) The spinning solution is sucked by a syringe, and the spinning solution is squeezed out through a needle. The extruded spinning solution enters a coagulation liquid to obtain a primary fiber. The primary fiber is sequentially subjected to a first mechanical drafting, a second mechanical drafting, a third mechanical drafting and a drafting box to obtain a stretched fiber. Finally, the stretched fiber is collected on a winding roller to obtain a modified polyacrylonitrile fiber. (7) After the modified polyacrylonitrile fiber and acetonitrile are evenly mixed, acrylamide is added and stirred for 1-2 hours at a stirring speed of 200-300 r / min, ethylene glycol dimethacrylate, perfluorooctylethylene and azobisisobutyronitrile are added, and the mixture is reacted at 60°C under nitrogen protection for 12-14 hours. The mixture is filtered and washed with pure water for 3-4 times, and dried at 60°C for 12-14 hours to obtain a super hydrophobic flame retardant fiber.
[0007] As an optimization, the preparation method of the pretreated polyacrylonitrile in step (1) is to mix polyacrylonitrile, sodium hydroxide and water in a mass ratio of 1:8-15:100-150, stir at 60°C for 1-2h, the stirring speed is 200r / min, filter and wash with pure water for 3-4 times, dry in a vacuum drying oven for 6-8h, the vacuum degree of the vacuum drying oven is 0.08MPa, the temperature is 50°C, and the molecular weight of polyacrylonitrile is 53000.
[0008] As an optimization, the preparation method of 5-mercaptosalicylic acid in step (3) is to stir 5-(sulfonyl chloride)salicylic acid, tin particles and concentrated hydrochloric acid in a mass ratio of 1:3-5:20-30 for 14-16 hours at a stirring speed of 200-300 r / min, cool to room temperature, filter, add ether in an amount equal to the volume of concentrated hydrochloric acid, filter again, take the filtrate, distill the filtrate under reduced pressure to remove the ether, and recrystallize with ethanol water to obtain 5-mercaptosalicylic acid, wherein the purity of the tin particles is greater than 99.99% and the particle size is 2-4 mm.
[0009] As an optimization, the silicon dioxide model in step (4) is HN-SP1, with a content greater than 99.5%, a particle size of 30 nm, and a specific surface area of 640 m 2 / g.
[0010] As an optimization, the preparation method of the tetramethylguanidinopropyltrimethoxysilane mixed solution in step (4) is to use glacial acetic acid to adjust the pH of 50wt% ethanol aqueous solution to 3.5-4.5, add tetramethylguanidinopropyltrimethoxysilane and mix evenly, wherein the mass volume ratio of tetramethylguanidinopropyltrimethoxysilane and 50wt% ethanol aqueous solution is 7-9:100.
[0011] As an optimization, the syringe used in step (6) has a specification of 20 mL, a needle inner diameter of 0.5 mm, an extrusion speed of 0.38-0.42 mL / min, a coagulation liquid prepared by mixing N,N-dimethylformamide and water in a volume ratio of 1:1, a first stretching roller speed of 20 r / min, a second stretching roller speed of 32 r / min, a third stretching roller speed of 36 r / min, a stretching box temperature of 115°C, and a winding roller speed of 38 r / min.
[0012] As an optimization, the amounts of modified polyacrylonitrile, acetonitrile, acrylamide, ethylene glycol dimethacrylate, perfluorooctylethylene, and azobisisobutyronitrile in step (7) are as follows, by mass: 7-9 parts of modified polyacrylonitrile, 50-60 parts of acetonitrile, 10-20 parts of acrylamide, 10-20 parts of ethylene glycol dimethacrylate, 7-8 parts of perfluorooctylethylene, and 1-3 parts of azobisisobutyronitrile.
[0013] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the super hydrophobic flame retardant fiber, the pretreated polyacrylonitrile is grafted with melamine, reacted with diallyl chlorophosphite, and then reacted with 5-mercaptosalicylic acid to obtain modified polyacrylonitrile; silicon dioxide is reacted with tetramethylguanidinopropyltrimethoxysilane to obtain modified silicon dioxide; the modified polyacrylonitrile and the modified silicon dioxide are blended and spun, and finally the super hydrophobic flame retardant fiber is finished with acrylamide and perfluorooctylethylene to obtain the super hydrophobic flame retardant fiber.
[0014] First, the pretreated polyacrylonitrile is grafted with melamine and then reacted with diallyl chlorophosphite, and then reacted with 5-mercaptosalicylic acid to obtain modified polyacrylonitrile; the polyacrylonitrile is pretreated with sodium hydroxide to perform alkaline hydrolysis on the polyacrylonitrile, and the cyano group in the polypropylene is converted into a carboxyl group, providing an active site for subsequent functional modification; then, the amino group of melamine and the carboxyl group on the polyacrylonitrile are subjected to a condensation reaction to introduce a nitrogen-based flame retardant on the surface of the polyacrylonitrile; diallyl chlorophosphite and the amino group of melamine are reacted to form a phosphorus-nitrogen-based flame retardant to provide good flame retardant properties for the polyacrylonitrile while introducing a double bond; the salicylic acid structure is introduced by utilizing the mercapto-ene click reaction between the mercapto group of 5-mercaptosalicylic acid and the double bond; the carbonyl group and the hydroxyl group in the salicylic acid structure can generate an internal hydrogen bond to form a chelate ring; after absorbing ultraviolet light energy, the molecular thermal vibration occurs, the internal hydrogen bond is destroyed, and the chelate ring is opened to convert the energy of the ultraviolet light into heat energy and release it, thereby giving the fiber prepared by the present invention the ability to resist ultraviolet light.
[0015] Secondly, silica is reacted with tetramethylguanidinopropyltrimethoxysilane to obtain modified silica. Tetramethylguanidinopropyltrimethoxysilane reacts with hydroxyl groups on the surface of silica to obtain hydrophobic silica. Guanidine groups with antibacterial effects are introduced onto the surface of silica to give silica certain antibacterial properties, thereby giving the fiber prepared by the present invention antibacterial ability.
[0016] Finally, modified polyacrylonitrile and modified silica are wet-spun to obtain modified polyacrylonitrile fibers, which are then finished with acrylamide and perfluorooctylethylene to obtain super-hydrophobic flame-retardant fibers. Modified polyacrylonitrile with salicylic acid structure and modified silica with guanidine group can be simply blended and neutralized to obtain quaternary ammonium salt spinning solution, and the fiber obtained from the spinning solution can further improve the antibacterial performance; after the neutralization reaction between modified polyacrylonitrile and modified silica, there are still some salicylic acid structures that have not participated in the reaction on the modified polyacrylonitrile, so the modified polypropylene after spinning There are unreacted salicylic acid structures on the fiber. The amide group in acrylamide forms a stable complex with the carboxyl group and phenolic hydroxyl group in salicylic acid through hydrogen bonds and electrostatic attraction. The ester group in ethylene glycol dimethacrylate can interact with acrylamide and salicylic acid. Azobisisobutyronitrile acts as a free radical initiator and decomposes to produce free radicals. These free radicals attack the unsaturated double bonds in acrylamide, ethylene glycol dimethacrylate and perfluorooctylethylene, thereby starting a polymerization reaction and fixing perfluorooctylethylene with low surface energy on the fiber, further increasing the hydrophobic properties of the fiber. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0018] The molecular weight of polyacrylonitrile used in all the following examples and comparative examples is 53,000, purchased from Shanghai Jinshan Petrochemical Co., Ltd.; the silicon dioxide is HN-SP1, with a content greater than 99.5%, a particle size of 30 nm, and a specific surface area of 640 m 2 / g, purchased from Zhejiang Zhoushan Mingri Nano Co., Ltd.; tin particles with a purity greater than 99.99% and a particle size of 2-4 mm were purchased from Nangong Yingtai Metal Materials Co., Ltd. Example 1
[0019] A method for preparing a super hydrophobic flame retardant fiber, the method for preparing the super hydrophobic flame retardant fiber comprising the following preparation steps: (1) Polyacrylonitrile, sodium hydroxide and water were mixed evenly in a mass ratio of 1:8:100, stirred at 60°C for 2 h at a stirring speed of 200 r / min, filtered and washed with pure water for 4 times, and dried in a vacuum drying oven for 8 h at a vacuum degree of 0.08 MPa and a temperature of 50°C; (2) Pretreated polyacrylonitrile, melamine, N,N-dicyclohexylcarbodiimide, N,N-dimethylformamide, and boric acid were mixed uniformly in a mass ratio of 1:1:0.5:100:0.1, reacted at 60°C for 4 hours, cooled to room temperature, added with dichloromethane 100 times the mass of pretreated polyacrylonitrile, filtered and washed with pure water for 3 times, and dried at 60°C for 14 hours to obtain melamine-modified polyacrylonitrile; (3) Melamine-modified polyacrylonitrile, acetonitrile and triethylamine were mixed in a mass ratio of 1:20:0.1 to obtain solution A; diallyl chlorophosphite was prepared into 2 g / mL solution B with acetonitrile; at 80°C, 0.02 times the volume of solution B was added dropwise to solution A at a rate of 0.25 mL / min. After the addition was completed, the reaction was continued for 6 hours, and 40 times the mass of melamine-modified polyacrylonitrile was added with dichloromethane, filtered and washed with pure water 3 times, and dried at 60°C for 14 hours to obtain a modified polyacrylonitrile precursor; (4) Stir 5-(sulfonyl chloride) salicylic acid, tin particles, and concentrated hydrochloric acid at a mass ratio of 1:3:20 for 16 h at a stirring speed of 200 r / min, cool to room temperature, filter, add ether in an amount equal to the volume of concentrated hydrochloric acid, filter again, take the filtrate, remove the ether by vacuum distillation, and recrystallize from ethanol water to obtain 5-mercaptosalicylic acid; (5) The modified polyacrylonitrile precursor, 5-mercaptosalicylic acid, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:2:20, 0.1 times the mass of the modified polyacrylonitrile precursor of 2,2-dimethoxy-2-phenylacetophenone was added, ultrasonicated at 40kHz for 30min, irradiated with ultraviolet light for 30min at room temperature with an ultraviolet light power of 500w, 40 times the mass of the modified polyacrylonitrile precursor of dichloromethane was added, filtered and washed with pure water for 3 times, and dried at 60°C for 14h to obtain modified polyacrylonitrile; (6) adjusting the pH of a 50 wt % ethanol aqueous solution to 3.5 using glacial acetic acid, adding tetramethylguanidinopropyltrimethoxysilane and mixing evenly to obtain a tetramethylguanidinopropyltrimethoxysilane mixed solution, wherein the mass volume ratio of tetramethylguanidinopropyltrimethoxysilane to the 50 wt % ethanol aqueous solution is 7:100; (7) Silica and anhydrous ethanol were mixed in a mass ratio of 1:20, and ultrasonically dispersed at 20 kHz for 20 min. A mixed solution of tetramethylguanidinopropyltrimethoxysilane with an equal volume of anhydrous ethanol was added, and stirred at 80°C for 4 h at a stirring speed of 500 r / min. After the stirring, the mixture was filtered, washed with pure water for 7 times, and dried at 60°C for 8 h to obtain modified silica. (8) Modified silica and N,N-dimethylformamide were mixed at a mass-to-volume ratio of 1:100, ultrasonicated at 40 kHz for 30 min, modified polyacrylonitrile in an amount 10 times the mass of the modified silica was added, stirred at 5 °C for 3 h at a stirring speed of 600 r / min, and ultrasonically defoamed at 40 kHz for 40 min to obtain a spinning solution; (9) The spinning solution was sucked by a 20 mL syringe, and the spinning solution was extruded through a needle with an inner diameter of 0.5 mm at an extrusion speed of 0.38 mL / min. The extruded spinning solution entered a coagulation liquid to obtain nascent fibers. The coagulation liquid was prepared by mixing N,N-dimethylformamide and water in a volume ratio of 1:1. The nascent fibers were sequentially subjected to one mechanical drawing, two mechanical drawing, three mechanical drawing and a drawing box to obtain stretched fibers. The speed of the first drawing roller was 20 r / min, the speed of the second drawing roller was 32 r / min, and the speed of the third drawing roller was 36 r / min. The temperature of the drawing box was 115 °C. Finally, the stretched fibers were collected on a winding roller. The speed of the winding roller was 38 r / min to obtain modified polyacrylonitrile fibers. (10) Weigh the following components by mass: 7 parts of modified polyacrylonitrile, 50 parts of acetonitrile, 10 parts of acrylamide, 10 parts of ethylene glycol dimethacrylate, 7 parts of perfluorooctylethylene, and 1 part of azobisisobutyronitrile. After uniformly mixing the modified polyacrylonitrile fiber and acetonitrile, add acrylamide and stir for 1 h at a stirring speed of 200 r / min. Then add ethylene glycol dimethacrylate, perfluorooctylethylene and azobisisobutyronitrile and react at 60°C for 12 h under nitrogen protection. Filter and wash three times with pure water and dry at 60°C for 12 h to obtain a super hydrophobic flame retardant fiber. Example 2
[0020] A method for preparing a super hydrophobic flame retardant fiber, the method for preparing the super hydrophobic flame retardant fiber comprising the following preparation steps: (1) Polyacrylonitrile, sodium hydroxide and water were mixed evenly in a mass ratio of 1:10:120, stirred at 60°C for 1.5 h at a stirring speed of 200 r / min, filtered and washed with pure water for 4 times, and dried in a vacuum drying oven for 7 h at a vacuum degree of 0.08 MPa and a temperature of 50°C; (2) Pretreated polyacrylonitrile, melamine, N,N-dicyclohexylcarbodiimide, N,N-dimethylformamide, and boric acid were mixed uniformly at a mass ratio of 1:1.5:0.7:110:0.15, reacted at 60°C for 4 hours, cooled to room temperature, added with dichloromethane 110 times the mass of pretreated polyacrylonitrile, filtered, washed with pure water for 4 times, and dried at 60°C for 13 hours to obtain melamine-modified polyacrylonitrile; (3) Melamine-modified polyacrylonitrile, acetonitrile and triethylamine were mixed in a mass ratio of 1:25:0.2 to obtain solution A; diallyl chlorophosphite was prepared into 2.5 g / mL solution B with acetonitrile; at 80°C, 0.03 times the volume of solution B was added dropwise to solution A at a rate of 0.25 mL / min. After the addition was completed, the reaction was continued for 7 hours, and 45 times the mass of melamine-modified polyacrylonitrile was added with dichloromethane, filtered and washed with pure water for 4 times, and dried at 60°C for 13 hours to obtain a modified polyacrylonitrile precursor; (4) Stir 5-(sulfonyl chloride) salicylic acid, tin particles, and concentrated hydrochloric acid in a mass ratio of 1:4:25 for 15 h at a stirring speed of 250 r / min, cool to room temperature, filter, add ether in an equal volume to the concentrated hydrochloric acid, filter again, take the filtrate, remove the ether by vacuum distillation, and recrystallize from ethanol water to obtain 5-mercaptosalicylic acid; (5) The modified polyacrylonitrile precursor, 5-mercaptosalicylic acid, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:2.5:25, 0.2 times the mass of the modified polyacrylonitrile precursor of 2,2-dimethoxy-2-phenylacetophenone was added, ultrasonicated at 25kHz for 25min, irradiated with ultraviolet light for 30min at room temperature with an ultraviolet light power of 500w, 45 times the mass of the modified polyacrylonitrile precursor of dichloromethane was added, filtered and washed with pure water for 3 times, and dried at 60°C for 13h to obtain modified polyacrylonitrile; (6) adjusting the pH of a 50 wt % ethanol aqueous solution to 4 using glacial acetic acid, adding tetramethylguanidinopropyltrimethoxysilane and mixing evenly to obtain a tetramethylguanidinopropyltrimethoxysilane mixed solution, wherein the mass volume ratio of tetramethylguanidinopropyltrimethoxysilane to the 50 wt % ethanol aqueous solution is 8:100; (7) Silica and anhydrous ethanol were mixed in a mass ratio of 1:25, ultrasonically dispersed at 30 kHz for 25 min, and a mixed solution of tetramethylguanidinopropyltrimethoxysilane of an equal volume to anhydrous ethanol was added, and stirred at 75°C for 4 h at a stirring speed of 450 r / min. After the stirring, the mixture was filtered, washed with pure water for 6 times, and dried at 60°C for 7 h to obtain modified silica; (8) Modified silica and N,N-dimethylformamide were mixed in a mass-to-volume ratio of 3:100, ultrasonically treated at 25 kHz for 35 min, modified polyacrylonitrile (15 times the mass of the modified silica) was added, stirred at 5°C for 2.5 h at a stirring speed of 500 r / min, and ultrasonically defoamed at 30 kHz for 35 min to obtain a spinning solution; (9) The spinning solution was sucked by a 20 mL syringe, and the spinning solution was extruded through a needle with an inner diameter of 0.5 mm at an extrusion speed of 0.40 mL / min. The extruded spinning solution entered the coagulation liquid to obtain the nascent fiber. The coagulation liquid was prepared by mixing N, N-dimethylformamide and water in a volume ratio of 1:1. The nascent fiber was sequentially subjected to one mechanical drawing, two mechanical drawing, three mechanical drawing and a drawing box to obtain the stretched fiber. The speed of the first drawing roller was 20 r / min, the speed of the second drawing roller was 32 r / min, and the speed of the third drawing roller was 36 r / min. The temperature of the drawing box was 115 °C. Finally, the stretched fiber was collected on a winding roller. The speed of the winding roller was 38 r / min to obtain modified polyacrylonitrile fiber. (10) Weigh 8 parts of modified polyacrylonitrile, 55 parts of acetonitrile, 15 parts of acrylamide, 15 parts of ethylene glycol dimethacrylate, 7 parts of perfluorooctylethylene, and 2 parts of azobisisobutyronitrile in proportion by mass, mix the modified polyacrylonitrile fiber and acetonitrile evenly, add acrylamide and stir for 1.5 h at a stirring speed of 250 r / min, add ethylene glycol dimethacrylate, perfluorooctylethylene and azobisisobutyronitrile, react for 13 h at 60°C under nitrogen protection, filter and wash three times with pure water, and dry at 60°C for 13 h to obtain a super hydrophobic flame retardant fiber. Example 3
[0021] A method for preparing a super hydrophobic flame retardant fiber, the method for preparing the super hydrophobic flame retardant fiber comprising the following preparation steps: (1) Polyacrylonitrile, sodium hydroxide and water were mixed evenly in a mass ratio of 1:15:150, stirred at 60°C for 1 h at a stirring speed of 200 r / min, filtered and washed with pure water for 4 times, and dried in a vacuum drying oven for 6 h at a vacuum degree of 0.08 MPa and a temperature of 50°C; (2) Pretreated polyacrylonitrile, melamine, N,N-dicyclohexylcarbodiimide, N,N-dimethylformamide, and boric acid were mixed uniformly in a mass ratio of 1:2:0.8:120:0.2, reacted at 60°C for 4 hours, cooled to room temperature, added with dichloromethane 120 times the mass of pretreated polyacrylonitrile, filtered, washed with pure water for 4 times, and dried at 60°C for 14 hours to obtain melamine-modified polyacrylonitrile; (3) Melamine-modified polyacrylonitrile, acetonitrile and triethylamine were mixed in a mass ratio of 1:30:0.3 to obtain solution A; diallyl chlorophosphite was prepared into 3 g / mL solution B with acetonitrile; at 80°C, 0.04 times the volume of solution B was added dropwise to solution A at a rate of 0.25 mL / min. After the addition was completed, the reaction was continued for 8 hours, and 50 times the mass of melamine-modified polyacrylonitrile was added with dichloromethane, filtered and washed with pure water for 4 times, and dried at 60°C for 12 hours to obtain a modified polyacrylonitrile precursor; (4) Stir 5-(sulfonyl chloride) salicylic acid, tin particles, and concentrated hydrochloric acid at a mass ratio of 1:5:30 for 14 h at a stirring speed of 300 r / min, cool to room temperature, filter, add ether in an equal volume to the concentrated hydrochloric acid, filter again, take the filtrate, remove the ether by vacuum distillation, and recrystallize from ethanol water to obtain 5-mercaptosalicylic acid; (5) The modified polyacrylonitrile precursor, 5-mercaptosalicylic acid, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:3:30, 0.3 times the mass of the modified polyacrylonitrile precursor of 2,2-dimethoxy-2-phenylacetophenone was added, ultrasonicated at 20kHz for 20min, irradiated with ultraviolet light for 30min at room temperature with an ultraviolet light power of 500w, 50 times the mass of the modified polyacrylonitrile precursor of dichloromethane was added, filtered and washed with pure water for 4 times, and dried at 60°C for 14h to obtain modified polyacrylonitrile; (6) adjusting the pH of a 50 wt % ethanol aqueous solution to 4.5 using glacial acetic acid, adding tetramethylguanidinopropyltrimethoxysilane and mixing evenly to obtain a tetramethylguanidinopropyltrimethoxysilane mixed solution, wherein the mass volume ratio of tetramethylguanidinopropyltrimethoxysilane to the 50 wt % ethanol aqueous solution is 9:100; (7) Silica and anhydrous ethanol were mixed in a mass ratio of 1:30, ultrasonically dispersed at 40 kHz for 30 min, and a mixed solution of tetramethylguanidinopropyltrimethoxysilane with an equal volume of anhydrous ethanol was added, and stirred at 60°C for 4 h at a stirring speed of 400 r / min. After the stirring, the mixture was filtered, washed with pure water for 7 times, and dried at 60°C for 8 h to obtain modified silica; (8) Modified silica and N,N-dimethylformamide were mixed in a mass-to-volume ratio of 5:100, ultrasonically treated at 40 kHz for 30 min, modified polyacrylonitrile (20 times the mass of the modified silica) was added, stirred at 8°C for 2 h at a stirring speed of 400 r / min, and ultrasonically defoamed at 20 kHz for 30 min to obtain a spinning solution; (9) The spinning solution was sucked by a 20 mL syringe, and the spinning solution was extruded through a needle with an inner diameter of 0.5 mm at an extrusion speed of 0.42 mL / min. The extruded spinning solution entered the coagulation liquid to obtain the nascent fiber. The coagulation liquid was prepared by mixing N, N-dimethylformamide and water in a volume ratio of 1:1. The nascent fiber was sequentially subjected to one mechanical drawing, two mechanical drawing, three mechanical drawing and a drawing box to obtain the stretched fiber. The speed of the first drawing roller was 20 r / min, the speed of the second drawing roller was 32 r / min, and the speed of the third drawing roller was 36 r / min. The temperature of the drawing box was 115 °C. Finally, the stretched fiber was collected on a winding roller. The speed of the winding roller was 38 r / min to obtain modified polyacrylonitrile fiber. (10) Weigh 9 parts of modified polyacrylonitrile, 60 parts of acetonitrile, 20 parts of acrylamide, 20 parts of ethylene glycol dimethacrylate, 8 parts of perfluorooctylethylene, and 3 parts of azobisisobutyronitrile in proportion by mass, mix the modified polyacrylonitrile fiber and acetonitrile evenly, add acrylamide and stir for 1 h at a stirring speed of 200 r / min, add ethylene glycol dimethacrylate, perfluorooctylethylene and azobisisobutyronitrile, react for 12 h at 60°C under nitrogen protection, filter and wash three times with pure water, and dry at 60°C for 12 h to obtain a super hydrophobic flame retardant fiber.
[0022] Comparative Example 1 The difference between the preparation method of the super hydrophobic flame retardant fiber of Comparative Example 1 and Example 2 is that steps (3), (4) and (5) are not performed, and step (8) is modified to mix the modified silica and N,N-dimethylformamide in a mass volume ratio of 3:100, ultrasonically treat at 25 kHz for 35 min, add melamine-modified polyacrylonitrile in an amount 15 times the mass of the modified silica, stir at 5°C for 2.5 h, and stir at a speed of 500 r / min, and ultrasonically defoam at 30 kHz for 35 min to obtain a spinning solution.
[0023] Comparative Example 2 The difference between the preparation method of the super hydrophobic flame retardant fiber of Comparative Example 2 and Example 2 is that steps (4) and (5) are not performed, and step (8) is modified to mix the modified silica and N,N-dimethylformamide in a mass volume ratio of 3:100, ultrasonically treat at 25 kHz for 35 min, add a modified polyacrylonitrile precursor with a mass of 15 times that of the modified silica, stir at 5°C for 2.5 h, and stir at a speed of 500 r / min, and ultrasonically defoam at 30 kHz for 35 min to obtain a spinning solution.
[0024] Comparative Example 3 The difference between the preparation method of the super hydrophobic flame retardant fiber of Comparative Example 3 and Example 2 is that steps (6) and (7) are not performed, and step (8) is modified to mix modified polyacrylonitrile and N,N-dimethylformamide in a mass volume ratio of 45:100, ultrasonically treat at 25 kHz for 35 min, stir at 5°C for 2.5 h, and stir at a speed of 500 r / min, and ultrasonically defoam at 30 kHz for 35 min to obtain a spinning solution.
[0025] Comparative Example 4 The difference between the preparation method of the super hydrophobic flame retardant fiber of comparative example 4 and that of embodiment 2 is that step (10) is not performed, and step (9) is modified to use a 20mL syringe to absorb the spinning solution, and extrude the spinning solution through a needle with an inner diameter of 0.5mm at an extrusion speed of 0.40mL / min. The extruded spinning solution enters the coagulation liquid to obtain the nascent fiber, and the coagulation liquid is prepared by mixing N,N-dimethylformamide and water in a volume ratio of 1:1. The nascent fiber is sequentially subjected to one mechanical drawing, two mechanical drawing, three mechanical drawing and a drawing box to obtain the stretched fiber, the first drawing roller speed is 20r / min, the second drawing roller speed is 32r / min, the third drawing roller speed is 36r / min, and the drawing box temperature is 115°C. Finally, the stretched fiber is collected on a winding roller, and the winding roller speed is 38r / min to obtain the super hydrophobic flame retardant fiber.
[0026] Test Example 1 Flame retardant performance test According to GB / T5454 standard, the super-hydrophobic flame-retardant fibers prepared in the embodiments and comparative examples were woven into fabrics and prepared into samples, and the limiting oxygen index of the samples was tested using a ZR-01 limiting oxygen index instrument. The results are shown in Table 1.
[0027] Table 1
[0028] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-4 in Table 1, it can be found that the super hydrophobic flame retardant fiber prepared in the present invention has good flame retardant properties.
[0029] By comparison, the limiting oxygen index of Examples 1-3 is greater than that of Comparative Example 1, indicating that the pretreatment of polyacrylonitrile with sodium hydroxide is to alkaline hydrolyze the polyacrylonitrile, convert the cyano group in the polypropylene into a carboxyl group, and provide an active site for subsequent functional modification. Subsequently, the amino group of melamine and the carboxyl group on the polyacrylonitrile are condensed to introduce a nitrogen-based flame retardant on the surface of the polyacrylonitrile, and then diallyl chlorophosphite is reacted with the amino group of melamine to form a phosphorus-nitrogen-based flame retardant to provide good flame retardant properties for the polyacrylonitrile.
[0030] Test Example 2 Hydrophobicity test The super-hydrophobic flame-retardant fibers prepared in each embodiment and comparative example were pasted on a glass slide and tested using a DSA20 contact angle tester. 5 μL of pure water was dropped on the surface of the super-hydrophobic flame-retardant fiber. The test was started after 60 seconds. Five points were measured and the average value was calculated after reading the data. The results are shown in Table 2.
[0031] Table 2
[0032] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-4 in Table 2, it can be found that the super hydrophobic flame retardant fiber prepared in the present invention has good hydrophobic properties.
[0033] By comparison, the contact angles of Examples 1-3 are greater than those of Comparative Examples 3 and 4, indicating that modified silica is prepared by reacting silica with tetramethylguanidinopropyltrimethoxysilane, and tetramethylguanidinopropyltrimethoxysilane reacts with hydroxyl groups on the surface of silica to obtain hydrophobic silica; after the neutralization reaction between modified polyacrylonitrile and modified silica, some salicylic acid structures that have not participated in the reaction still exist on the modified polyacrylonitrile, so unreacted salicylic acid structures exist on the modified polypropylene fiber after spinning, the amide group in acrylamide forms a stable complex with the carboxyl group and phenolic hydroxyl group in salicylic acid through hydrogen bonds and electrostatic attraction, the ester group in ethylene glycol dimethacrylate can interact with acrylamide and salicylic acid, and azobisisobutyronitrile, as a free radical initiator, decomposes to generate free radicals, and these free radicals attack the unsaturated double bonds in acrylamide, ethylene glycol dimethacrylate and perfluorooctylethylene, thereby starting a polymerization reaction, fixing perfluorooctylethylene with low surface energy on the fiber, and further increasing the hydrophobicity of the fiber.
[0034] Test Example 3 UV resistance test The super-hydrophobic flame-retardant fibers prepared in the examples and comparative examples were woven into plain fabrics on a weaving trolley, with warp and weft densities of 107 strands / inch and 63 strands / inch, respectively, and the UV transmittance of the plain fabrics was tested at 370 nm using a Varian Cary 500 UV-visible integrating sphere spectrophotometer. The results are shown in Table 3.
[0035] Table 3
[0036] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-4 in Table 3, it can be found that the super hydrophobic flame retardant fiber prepared in the present invention has good anti-ultraviolet performance.
[0037] By comparison, the UV transmittance of Examples 1-3 is lower than that of Comparative Examples 1-3, indicating that sodium hydroxide is used to alkaline hydrolyze polyacrylonitrile to convert the cyano group in polypropylene into a carboxyl group, thereby providing an active site for subsequent functional modification, and then the amino group of melamine and the carboxyl group on polyacrylonitrile are subjected to a condensation reaction, and then the double bond is introduced while using the reaction energy of diallyl chlorophosphite and the amino group of melamine, and the salicylic acid structure is introduced by utilizing the thiol group of 5-mercaptosalicylic acid and the thiol-ene click reaction of the double bond, and the carbonyl group and the hydroxyl group in the salicylic acid structure can generate an intrinsic hydrogen bond to form a chelate ring, which, after absorbing ultraviolet light energy, undergoes molecular thermal vibration, destroys the intrinsic hydrogen bond, and opens the chelate ring to convert the energy of ultraviolet light into heat energy and release it, thereby giving the fiber prepared by the present invention the ability to resist ultraviolet light.
[0038] Test Example 4 Antimicrobial performance testing The antibacterial properties of the super-hydrophobic flame-retardant fibers prepared in the examples and comparative examples were tested using the oscillation method in GB / T20944.3-2008 "Evaluation of Antibacterial Properties of Textiles". The results are shown in Table 4.
[0039] Table 4
[0040] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-4 in Table 4, it can be found that the super hydrophobic flame retardant fiber prepared in the present invention has good antibacterial properties.
[0041] By comparison, the antibacterial rates of Examples 1-3 are greater than that of Comparative Example 3, indicating that silica is reacted with tetramethylguanidinopropyltrimethoxysilane to obtain modified silica, and tetramethylguanidinopropyltrimethoxysilane reacts with hydroxyl groups on the surface of silica to introduce guanidine groups with antibacterial effects on the surface of silica, giving silica certain antibacterial properties, thereby giving the fiber prepared by the present invention antibacterial ability; finally, modified polyacrylonitrile and modified silica are wet-spun to obtain modified polyacrylonitrile fibers, which are finished with acrylamide and perfluorooctylethylene to obtain super-hydrophobic flame-retardant fibers, and modified polyacrylonitrile with a salicylic acid structure and modified silica with guanidine groups can be simply blended and neutralized to obtain a quaternary ammonium salt spinning solution, and the fiber prepared from the spinning solution can further improve the antibacterial properties.
[0042] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A super hydrophobic flame retardant fiber, characterized in that: The super hydrophobic flame retardant fiber is prepared by grafting melamine onto pretreated polyacrylonitrile, reacting with diallyl chlorophosphite, and then reacting with 5-mercaptosalicylic acid to obtain modified polyacrylonitrile; reacting silica with tetramethylguanidinopropyltrimethoxysilane to obtain modified silica; blending the modified polyacrylonitrile and the modified silica for spinning, and finally finishing with acrylamide and perfluorooctylethylene to obtain the super hydrophobic flame retardant fiber.
2. A method for preparing a super hydrophobic flame retardant fiber, characterized in that: The method comprises the following preparation steps: (1) Pretreated polyacrylonitrile, melamine, N,N-dicyclohexylcarbodiimide, N,N-dimethylformamide, and boric acid were mixed uniformly in a mass ratio of 1:1-2:0.5-0.8:100-120:0.1-0.2, reacted at 60°C for 4 hours, cooled to room temperature, added with dichloromethane 100-120 times the mass of pretreated polyacrylonitrile, filtered and washed with pure water for 3-4 times, and dried at 60°C for 12-14 hours to obtain melamine-modified polyacrylonitrile; (2) Mix melamine-modified polyacrylonitrile, acetonitrile and triethylamine in a mass ratio of 1:20-30:0.1-0.3 to obtain solution A; prepare diallyl chlorophosphite with acetonitrile to prepare solution B with a concentration of 2-3 g / mL; add solution B (0.02-0.04 times the volume of solution A) dropwise to solution A at 80°C at a rate of 0.25 mL / min. After the addition is completed, continue the reaction for 6-8 hours, add dichloromethane (40-50 times the mass of the melamine-modified polyacrylonitrile), filter and wash with pure water for 3-4 times, and dry at 60°C for 12-14 hours to obtain a modified polyacrylonitrile precursor; (3) The modified polyacrylonitrile precursor, 5-mercaptosalicylic acid, and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:2-3:20-30, 0.1-0.3 times the mass of the modified polyacrylonitrile precursor of 2,2-dimethoxy-2-phenylacetophenone is added, ultrasonication is performed at 20-40kHz for 20-30 minutes, ultraviolet light is irradiated at room temperature for 30 minutes, and the ultraviolet light power is 500w. Then, 40-50 times the mass of the modified polyacrylonitrile precursor of dichloromethane is added, the mixture is filtered and washed with pure water for 3-4 times, and dried at 60°C for 12-14h to obtain modified polyacrylonitrile; (4) Mix silica and anhydrous ethanol in a mass ratio of 1:20-30, disperse them ultrasonically at 20-40kHz for 20-30min, add a mixed solution of tetramethylguanidinopropyltrimethoxysilane in an equal volume to anhydrous ethanol, stir at 60-80°C for 4h at a stirring speed of 400-500r / min, filter after stirring, wash with pure water for 5-7 times, and dry at 60°C for 6-8h to obtain modified silica; (5) Mixing modified silica and N,N-dimethylformamide in a mass-to-volume ratio of 1-5:100, ultrasonically treating at 20-40 kHz for 30-40 min, adding modified polyacrylonitrile in an amount 10-20 times the mass of the modified silica, stirring at 5-10° C. for 2-3 h at a stirring speed of 400-600 r / min, and ultrasonically defoaming at 20-40 kHz for 30-40 min to obtain a spinning solution; (6) The spinning solution is sucked by a syringe, and the spinning solution is squeezed out through a needle. The extruded spinning solution enters a coagulation liquid to obtain a primary fiber. The primary fiber is sequentially subjected to a first mechanical drafting, a second mechanical drafting, a third mechanical drafting and a drafting box to obtain a stretched fiber. Finally, the stretched fiber is collected on a winding roller to obtain a modified polyacrylonitrile fiber. (7) After the modified polyacrylonitrile fiber and acetonitrile are evenly mixed, acrylamide is added and stirred for 1-2 hours at a stirring speed of 200-300 r / min, ethylene glycol dimethacrylate, perfluorooctylethylene and azobisisobutyronitrile are added, and the mixture is reacted at 60°C under nitrogen protection for 12-14 hours. The mixture is filtered and washed with pure water for 3-4 times, and dried at 60°C for 12-14 hours to obtain a super hydrophobic flame retardant fiber.
3. The method for preparing a super hydrophobic flame retardant fiber according to claim 2, characterized in that: The preparation method of the pretreated polyacrylonitrile in step (1) is to uniformly mix polyacrylonitrile, sodium hydroxide and water in a mass ratio of 1:8-15:100-150, stir at 60°C for 1-2h, at a stirring speed of 200r / min, filter and wash with pure water for 3-4 times, and dry in a vacuum drying oven for 6-8h, wherein the vacuum degree of the vacuum drying oven is 0.08MPa and the temperature is 50°C, and the molecular weight of the polyacrylonitrile is 53000.
4. The method for preparing a super hydrophobic flame retardant fiber according to claim 2, characterized in that: The preparation method of 5-mercaptosalicylic acid in step (3) is as follows: 5-(sulfonyl chloride)salicylic acid, tin particles, and concentrated hydrochloric acid are stirred at a mass ratio of 1:3-5:20-30 for 14-16 hours at a stirring speed of 200-300 r / min, cooled to room temperature, filtered, and an equal volume of ether to the concentrated hydrochloric acid is added, filtered again, and the filtrate is taken. The ether is removed by vacuum distillation of the filtrate, and 5-mercaptosalicylic acid is obtained by recrystallization with ethanol water. The purity of the tin particles is greater than 99.99%, and the particle size is 2-4 mm.
5. The method for preparing a super hydrophobic flame retardant fiber according to claim 2, characterized in that: The silicon dioxide model in step (4) is HN-SP1, with a content greater than 99.5%, a particle size of 30 nm, and a specific surface area of 640 m 2 / g.
6. The method for preparing a super hydrophobic flame retardant fiber according to claim 2, characterized in that: The preparation method of the tetramethylguanidinopropyltrimethoxysilane mixed solution in step (4) is to use glacial acetic acid to adjust the pH of 50wt% ethanol aqueous solution to 3.5-4.5, add tetramethylguanidinopropyltrimethoxysilane and mix evenly, wherein the mass volume ratio of tetramethylguanidinopropyltrimethoxysilane to 50wt% ethanol aqueous solution is 7-9:
100.
7. The method for preparing a super hydrophobic flame retardant fiber according to claim 2, characterized in that: The syringe used in step (6) has a specification of 20 mL, a needle inner diameter of 0.5 mm, an extrusion speed of 0.38-0.42 mL / min, a coagulation liquid prepared by mixing N,N-dimethylformamide and water in a volume ratio of 1:1, a first stretching roller speed of 20 r / min, a second stretching roller speed of 32 r / min, a third stretching roller speed of 36 r / min, a stretching box temperature of 115°C, and a winding roller speed of 38 r / min.
8. The method for preparing a super hydrophobic flame retardant fiber according to claim 2, characterized in that: The amounts of modified polyacrylonitrile, acetonitrile, acrylamide, ethylene glycol dimethacrylate, perfluorooctylethylene, and azobisisobutyronitrile used in step (7) are as follows, by mass: 7-9 parts of modified polyacrylonitrile, 50-60 parts of acetonitrile, 10-20 parts of acrylamide, 10-20 parts of ethylene glycol dimethacrylate, 7-8 parts of perfluorooctylethylene, and 1-3 parts of azobisisobutyronitrile.
Citation Information
Patent Citations
Ultraviolet-cured organic silicon / silicon dioxide hybrid super-hydrophobic fabric and preparation method thereof
CN111021043A
Dyeing process flow of flame-retardant thread
CN112921676A
Intumescent flame retardant, preparation method and application of intumescent flame retardant, flame-retardant polyacrylonitrile fiber and preparation method of flame-retardant polyacrylonitrile fiber
CN114437366A
Breathable garment material and preparation method thereof
CN118927721A
Cited By
Hollow porous flame-retardant fiber and preparation method thereof
CN121321274A
